The application of SUDEP in forensic diagnosis: a mini review - Sun, Daming; Wang, Qiang (Frontiers in Neurology, 2023)
In the epilepsy population, sudden death from epilepsy is a rare occurrence but is nearly 24 times greater risk than sudden death from other causes. Sudden unexpected death in epilepsy (SUDEP) has been widely recognized in clinical studies. Despite its importance as a cause of death, SUDEP is rarely used in forensic practice. This review focuses on the forensic characteristics of SUDEP, analyzes the reasons for its underuse in forensic practice, and illustrates the prospect of establishing uniform diagnostic criteria for sudden unexpected death in epilepsy and molecular anatomy in aiding forensic diagnosis.